A simple technique for road surface modelling. Issue 3 (2nd July 2016) - El-Ashmawy, Khalid L. A.
Abstract: Road surface survey is critical for road engineers to determine the needs of maintenance and rehabilitation for both network and project level study. This paper reviews the road surface survey methods, including image based, photogrammetric and stereo-vision, and mobile mapping systems. The merits and demerits of each method are outlined. The goal of this study is to develop simple software for facilitating the generation of the necessary road surface and distresses maps using surveying data from different sources. The software output has compatibility with known CAD/GIS packages to widen its scope of applications. Methodologies, examples and demonstration related to the use of the developed software and laser scanning data in road mapping for a case study are described. The results showed the flexibilities of the developed software and the proposed method for generating the necessary maps and data for road distresses such as longitudinal cracks, transverse cracks, patch deterioration, potholes, and ravelling. However, the present work shows that using terrestrial laser scanning technologies for modelling the road surface has advantages such as surveying speed, big roads, highways and tunnels. Also it provides the safety for surveyors and the absence of a disruption to traffic. The developed software and methodology are suitable for universities, academic centres and are of great interest to small engineering firms for the generation of road surface maps.